2012
DOI: 10.1097/ccm.0b013e31822d7c18
|View full text |Cite
|
Sign up to set email alerts
|

Muscle atrophy and preferential loss of myosin in prolonged critically ill patients*

Abstract: Both limb and abdominal wall skeletal muscles of prolonged critically ill patients showed downregulation of protein synthesis at the gene expression level as well as increased proteolysis. This affected myosin to a greater extent than actin, resulting in a decreased myosin/actin ratio. Muscle atrophy was not ameliorated by intensive insulin therapy, but possibly aggravated by corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 12 publications
5
114
0
9
Order By: Relevance
“…In fact, the initial studies did not investigate whether autophagy is sufficiently activated to cope with the severe damage inflicted by critical illness. However, a clinical study that considered consequences of insufficient autophagy confirmed similar changes in skeletal muscle and liver of critically ill patients as observed in autophagy-deficient mice (FIGURE 10) (154,728). These included the accumulation of ubiquitin aggregates and other autophagy substrates, such as p62, deformed mitochondria, and aberrant concentric membranous structures.…”
Section: Autophagy In Critical Illnessmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, the initial studies did not investigate whether autophagy is sufficiently activated to cope with the severe damage inflicted by critical illness. However, a clinical study that considered consequences of insufficient autophagy confirmed similar changes in skeletal muscle and liver of critically ill patients as observed in autophagy-deficient mice (FIGURE 10) (154,728). These included the accumulation of ubiquitin aggregates and other autophagy substrates, such as p62, deformed mitochondria, and aberrant concentric membranous structures.…”
Section: Autophagy In Critical Illnessmentioning
confidence: 98%
“…Interestingly, proteasome activity was also elevated by 30% in serratus anterior, a muscle of the rib cage. In rectus abdomi- nis muscle, a more than twofold increase in chymotrypsinlike activity of the 20S-proteasome has been described (154). Such functional readouts are certainly more informative and preferable over simple transcript or protein content analyses which may not account for the temporary nature of mRNA levels, which can be as short-lived and fall quickly during prolonged muscle proteolysis (409).…”
Section: A the Ubiquitin-proteasome Pathway In Critical Illnessmentioning
confidence: 99%
“…Therefore, our finding that MS-275 completely prevented the decrease in specific force in 10-dayimmobilized muscles suggests that class I HDACs contribute to contractile dysfunction during disuse. There are several potential mechanisms that might contribute to contractile dysfunction during muscle disuse, including (but not limited to) shifts in myosin isoforms (Caiozzo et al, 1998;Caiozzo et al, 1996;Campione et al, 1993;Fitts et al, 2000), alterations in Ca 2+ release and sensitivity (Fraysse et al, 2003), and the preferential degradation of myosin heavy chain (MHC) (Derde et al, 2012;Ochala et al, 2011), which is mediated through the FoxO target gene MuRF1 . Because we found that HDAC1 was necessary for both activation of FoxO and the expression of MuRF1, and MS-275 preferentially inhibits HDAC1, we hypothesized that the preservation of specific force might be related to the sparing of MHC.…”
Section: Inhibition Of Class I Hdacs During Skeletal Muscle Disuse Prmentioning
confidence: 99%
“…On the other hand, Derde et al [110], using muscle biopsy samples, demonstrated that IIT does not affect myofiber size, myofibrillar protein synthesis ability, or muscle proteolytic markers. ITT is considered to primarily have a neuroprotective role [107], but no neurological data are available.…”
Section: Intensive Insulin Treatmentmentioning
confidence: 99%